Environmental planning and management in the ADB project cycle. (Manila Asian Development Bank, 1995)
Protecting the environment and managing natural resources are top priorities for governments and development institutions worldwide. The Asian Development Bank, the premier development agency in the Asia-Pacific region since its founding in 1966 is no exception to this rule. Through its Office of Environment and Social Development, the ADB's environment program includes loans and grants; institutional building; research, education and training; and related components. The ADB carefully assesses the environmental impact of each of its loan projects. It is a thorough, exhaustive review. The presentation examines the Bank;s project cycle from inception to completion.
Keywords: Environmental policy -- Asia. .